Indeks Gonadosomatik dan Struktur Histologis Gonad Ikan Uceng (Nemacheilus fasciatus, Valenciennes in Cuvier and Valenciennes, 1846) - Luthfi Nurhidayat; Febrina Nanda Arfiani; Bambang Retnoaji (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2017)
Uceng fish is wild native fish of Indonesia that live in fresh water river. It is very common that people consume the fish for it high protein contain. High demand of fish availability cause the fish exploitation increasing rapidly in nature. The high intensity of fish exploitation, soon will induce declining population of the fish and leading to extinction. Uceng fish cultivation is one alternative to solve the tread. The purpose of this research is to examine the Gonadosomatic Index (GSI) and gonad histological structure of male and female uceng fish (Nemacheilus fasciatus) on the period of immature and mature. Fish were dissected , weighed and the gonads were measured for gonadosomatic index. Moreover, gonad were fixed in NBF 5% for histological preparation by paraffin method and which than were stained by Hematoxylin-Eosin. The result were analyzed for both qualitatively and quantitatively. Qualitative analysis was conducted for gonad histological structure of male and female fish, while quantitative analysis was for Gonadosomatic Index (GSI) of fish respectively. The result showed that there were differences on the gonadosomatic index of males and females fish, the histological structure of ovarian follicle and the composition of the spermatogenic cells of immature gonads and mature gonads of the fish respectively. It was conclude that there are differences on Gonadosomatic Index and gonad histological structure on immature and mature of male and female of Uceng fish (N. fasciatus).